Thermo-mechanical behaviour of rocks from the Busveld Igneous Complex with relevance to deeper mining - Oniyide, Gafar (My University, 2016)
The Bushveld Igneous Complex (BIC) is the world’s largest layered igneous intrusion. It is about seven to nine kilometres thick and divided into eastern, western and northern limbs. Its upper critical zone hosts the world’s largest deposit of platinum group elements (PGE). The Merensky Reef has been traced for 300 km around the entire outcrop of the eastern and western limbs of the BIC, and to depths of 5 km and beyond. The temperature gradient of the BIC approximately doubles that of the Witwatersrand Basin, which makes the platinum mines face more heat challenges with increasing depth of mining than their counterparts in the gold mines. Rock lithology at great depth are subjected to high virgin temperatures and stresses before mining. The air temperature reduces down to around 27 to 30°C for workers’ comfort, while exposed rock surface would still have higher temperatures than the mine air. The response of rock to temperature variation, coupled with increased in-situ stresses, may pose serious challenges to the future of platinum mining in South Africa. From the literature survey, it has been established that variation in temperature has influence on the behaviour of rocks. These effects have been studied for cases of underground fire accidents, thermal repositories, geothermal intrusions and underground storage caverns. The question as to what would be the influence of virgin rock temperature on the behaviour of rock and the stability of underground openings, particularly those located in areas of high geothermal gradient remains unanswered. This thesis presents the results of investigation on the response of rocks, particularly from BIC, to variation of temperature from rock engineering point of view through laboratory, microscopic and numerical analyses. The uniaxial and triaxial compression testing of the specimens at various temperatures were carried out using MTS 793 servo-controlled testing machine. The results of the laboratory testing revealed that increase in temperature led to reduction in the Young’s modulus and peak strength of the rocks and increase in the coefficient of thermal expansion as well as dilation angle. From the Young’s modulus and yield strength, determined in the laboratory, relationship between Young’s modulus, temperature and strength versus temperature, were developed. The microscopic analyses examine the effect of heat on rocks from the BIC, in terms of initiation or extension of micro-cracks in the rock structure and changes in their chemical composition. Optical and scanning electron microscopes were used for image capturing. The results of the optical microscope analyses show that there are some physical changes observed on the rocks subjected to heat treatment, however, the observed changes are not significant. The scanning electron microscope images revealed that crack initiation starts at lower temperature and extends with increasing temperature. The chemical analyses of the specimen show that the temperature range considered for this research is not high enough to induce chemical changes in the specimens. The numerical analyses looked into the effect of temperature on the behaviour of underground excavations by considering variation of temperature and in-situ stresses with increasing mining depth. Comparisons were made for mining at depths of 1073, 2835 and 5038 m below surface. The general observation is that the increase in the in-situ stress and temperature led to higher scale of failure around the excavation with corresponding depth increase. At depth of 1073 m, there was no observation of shear and tensile failure. At depth of 2835 m, shear and tensile failure became evidenced in the state, convergence and failure plots. The tensile and shear failures at depth of 5038 m is quite high due to the high temperature and in-situ stresses. There were increases in the magnitudes of the horizontal and vertical convergence at this depth. Recommendations were made on appropriate support systems that would suit the rock behaviour at deep mining levels. A sensitivity analysis was done to evaluate the influence of increasing temperature on failure. This was achieved by assigning the temperature (50°C) and thermal properties for 1073 m below surface to depth of 5038 m. Similarly, temperature (140°C) and the thermal properties of 5038 m was assigned to 1073 m, while keeping the in-situ stresses and all other modelling parameters constant. Reduction of temperature and thermal properties at 5038 m resulted in the reduction of the extent of tensile and shear failures. The reverse was observed at 1073 m due to temperature increase. Generally, the numerical modelling revealed that the extent of tensile failure is a function of excavation geometry, temperature and in-situ stresses.